IMPLEMENTASI METODE SOSTAS PADA INOVASI DIGITAL MARKETING PRODUK KRIPIK SALAK SEMERU - Irwanto, Jesi; Fauziah, Anisatul (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
This research has the objective of developing a digital marketing strategy for micro, small and medium enterprises making semeru lumajang salak chips. The qualitative methodological approach is a research approach, in which the data collection process is carried out through the observations of research respondents to obtain meaning related to the essential phenomena that occur. The results of the research that has been carried out are